Application of FT-IR technique to bituminous materials - Zofka, Adam; Maliszewska, Dominika; Maliszewski, Maciej (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Spectroscopy is a fundamental method used in the material science that relies on the interaction of the electromagnetic radiation with a matter. Infrared spectroscopy allows for material fingerprinting as well as detection and quantification of compounds in a sample. In principle, IR spectrometers record the absorption of electromagnetic energy by chemical bounds in a sample as a function of wavelength. Chemical bounds have unique spectra bands at specific wavelengths regardless of the composition of the remaining molecular structure. The absorbance at these specific wavelengths can be used to quantify a particular functional group in the analyzed material. Absorbance peaks are easily identified on the IR spectra and can be used to fingerprint a compound in a mixture, especially when compared to the original unmodified IR spectra. In the recent years, the FT-IR method has become a popular tool for the quality assurance in the practical applications as well as it became a very useful tool in studying various construction materials, e.g. portland cement, bitumen, etc.